Aktivitas Pengelolaan Wisata Petualangan Canyoning Berbasis Resiko: Studi Kasus di Kawasan Canyoning & Caving Bogor Indonesia - Agung Yuliyanto Nugroho; Suswanto Suswanto; Sri Yulianto Fajar Pradap; Herra Herryani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Canyoning adventure tourism is a form of nature tourism activity that provides extreme and challenging experiences for tourists. However, the high level of risk in this activity requires a comprehensive risk management approach to ensure the safety and comfort of participants. This study aims to analyze risk-based canyoning tourism management activities in the Canyoning & Caving area, Bogor, Indonesia. This study uses a qualitative method with data collection techniques in the form of in-depth interviews with tour managers, canyoning guides, and tourists who have participated in the activity. In addition, direct observations were made of field conditions and facilities provided. The results of the study indicate that the implementation of effective risk management is very important to minimize the potential for accidents and negative impacts on the environment. Some of the main risks identified include unpredictable weather conditions, terrain difficulty, and lack of participant experience. The risk mitigation strategies implemented include intensive training for guides, the use of international standard safety equipment, and the preparation of clear emergency procedures. This study is expected to be a reference for other canyoning tourism managers in developing safe and sustainable adventure tourism in Indonesia.